SPIN 2004 : (World Scientific, 2005)
This comprehensive volume covers the most recent advances in the field of spin physics, including the latest research in high energy and nuclear physics and the study of nuclear spin structure. The comprehensive coverage also includes polarized proton and electron acceleration and storage, as well as polarized ion sources and targets.